Gamma irradiation-induced genetic variability and its effects on the phenotypic and agronomic traits of groundnut (Arachis hypogaeaL.) - Saibari, Imane; Barrijal, Saïd; Mouhib, Mohammed; Belkadi, Najlae; Hamim, Ahlam (Frontiers in Genetics, 2023)
In order to increase genetic variability for the improvement of groundnut, two varieties, namely Kp29 and Fleur11, were treated with six different gamma irradiation doses. A significant effect of mutagenesis was distinctly observed in the stem lengths, roots, and survival percentage in both varieties. The radio-sensitivity test showed a mean lethal dose of 436.51Gy for Kp29 and 501.18 Gy for Fleur11. Furthermore, this study revealed putative mutants with variable agro-morphological traits. Seven chlorophyll mutants and various seed shape and color mutants were obtained. This study demonstrates the potency of gamma irradiation to induce high genetic variability that led to the emergence of certain mutations of economic importance.